2013
DOI: 10.1039/c3nr34181j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface morphology on friction of graphene on various substrates

Abstract: The friction of graphene on various substrates, such as SiO2, h-BN, bulk-like graphene, and mica, was investigated to characterize the adhesion level between graphene and the underlying surface. The friction of graphene on SiO2 decreased with increasing thickness and converged around the penta-layers due to incomplete contact between the two surfaces. However, the friction of graphene on an atomically flat substrate, such as h-BN or bulk-like graphene, was low and comparable to that of bulk-like graphene. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 40 publications
2
103
1
1
Order By: Relevance
“…Considering that surface topography can significantly affect the friction characteristics of two-dimensional materials [20,23], the MoS 2 specimens were examined using AFM prior to the friction loop measurements. The AFM topographic images of mechanically exfoliated single-layer MoS 2 and CVD-grown single-layer MoS 2 at 800 °C , 850 °C , and 900 °C obtained with the intermittent contact mode are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that surface topography can significantly affect the friction characteristics of two-dimensional materials [20,23], the MoS 2 specimens were examined using AFM prior to the friction loop measurements. The AFM topographic images of mechanically exfoliated single-layer MoS 2 and CVD-grown single-layer MoS 2 at 800 °C , 850 °C , and 900 °C obtained with the intermittent contact mode are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors, such as the number of layers [14,17], surface topography [20,23], interactions with the substrate [21], and crystalline orientation [18] can affect the friction characteristics of two-dimensional materials, in addition to the experimental and environmental conditions [24]. The dependence of |www.Springer.com/journal/40544 | Friction http://friction.tsinghuajournals.com MoS 2 friction characteristics on the surface topography is not clearly indicated in Figs.…”
Section: E and 1gmentioning
confidence: 99%
“…Based on solid experimental evidence and finite-element modeling, they suggested that this trend arises from the increase in the susceptibility of the thinner sheet to out-of-plane elastic deformation. Recently, they went a step further and determined the effect of surface morphology on friction with graphene [58]. These measurements revealed that graphene maintains its corrugation level even after it is refolded onto an atomically flat substrate and that both the graphene and the substrate must be ultraflat to achieve the intimate contact necessary for strong adhesion and low friction.…”
Section: Dependence Of Friction On Layer Number and Substratementioning
confidence: 99%
“…7,12 This dependence could be different for various materials or morphologies of the substrate because of the variation of the adhesive force between substrate and graphene. [12][13][14] The adhesion between atomic force microscope (AFM) probe and graphene can also affect the friction force and lead to the emergence of an effectively negative friction coefficient. 15 Meanwhile, electro-phonon coupling and shear deformations were also brought to explain the energy dissipation mechanism during the friction process.…”
Section: Introductionmentioning
confidence: 99%